Cross-platform gendertrolling: a case study on a prominent harassment case in Brazil - Santini, Rose Marie; Salles, Débora; Belisario, Adriano; Belin, Luciane L. (AoIR Selected Papers of Internet Research, 2026)
This study investigates evidences of cross-platform gendertrolling in a high-profile Brazilian sexual harassment case. Gendertrolling is a form of technology-facilitated gender-based violence where individuals become targets of coordinated cyber harassment. It aims to destabilize victims, manipulate organic interactions, and disrupt women’s participation in social media. While online misogyny has been the subject of recent studies, little research has examined its cross-platform dynamics, particularly in the Global South. In this paper, we propose a case study of one of Brazil’s most prominent sexual harassment allegations involving celebrities from the country’s largest television network, Rede Globo. In 2019, twelve women accused their former boss of harassment and/or attempted rape. The research analyzes 164 YouTube videos about the case, posted by the accused man and a supporter, and 64.7K comments, posted between June 2022 and July 2023, along with 1,436 Instagram comments from marketing campaigns featuring the main accuser. Using anomaly detection algorithms, natural language processing, and network analysis, we identify spikes in hostile comments following pro-defendant YouTube live streams. Engagement on Instagram surged after YouTube discussions, suggesting cross-platform incitement. Findings indicate that 84% of Instagram comments were attacks on the victim, with repetitive phrases and emojis signaling potential coordination. However, the right-skewed comment distribution suggests a mix of orchestrated and organic participation. Live streams acted as mobilization points, reinforcing narratives that fueled reputational attacks. This study provides empirical evidence of cross-platform misogynistic campaigns, highlighting the role of live streams in digital gendered violence.